A natural acoustic front-end for interactive TV in the EU-project DICIT - Marquardt, Lutz; Svaizer, P.; Mabande, Edwin; Brutti, A.; Zieger, C.; Omologo, M.; Kellermann, Walter (PACRIM 2009 - 2009 IEEE Pacific Rim Conference on Communications, Computers and Signal Processing, 2009)
"Distant-talking Interfaces for Control of Interactive TV" (DICIT) is a European Union-funded project whose main objective is to integrate distant-talking voice interaction as a complementary modality to the use of a remote control in interactive TV systems. Hands-free and seamless control enables a natural user-system interaction providing a suitable means to greatly ease information retrieval. In the given living room scenario the system recognizes commands spoken by multiple and possibly moving users, even in the presence of background noise and TV surround audio. This paper focuses on the multichannel acoustic front-end (MCAF) processing for acoustic scene interpretation which is based on the combination of multi-channel acoustic echo cancellation, blind source separation, beamform-ing, acoustic event classification, and multiple speaker localization. The fully functional DICIT prototype consists of the MCAF, automatic speech recognition, natural language understanding, mixed-initiative dialogue and satellite connection. © 2009 IEE